PENGARUH KERAPATAN KAYU, TEKANAN PENGEMPAAN DAN JENIS PEREKAT TERHADAP SIFAT BRIKET KAYU - R Sudradjat (Jurnal Penelitian Hasil Hutan, 1984)
Chips of eight wood species were milled and briquette with varying pressure. Cassava flour and molasse were used as binders.            Briquette density ranged from 0,875 to 1.037 g/cm3; compressive strength from 216.32 to 604.12 kg/cm2; calorific value from 4318 to 4668 cal./g, moisture content from 3.58 to 6.12%, and ash content from 1.61 to 3.91%.             Higher density woods produced higher density briquette but lower in moisture and ash contents. Briquettes bonded with cassava flour were higher in density and ash content but lower in compressive strength and calorific value.             The relationship between pressing pressure and briquette density can be expressed in a linear regression equation. The effect of pressing pressure on compressive strength follows a quadratic regression equation for briquettes bonded with molasse.